EFEKTIVITAS PENGGUNAAN VIRTUAL LABORATORY TERHADAP PENINGKATAN HASIL BELAJAR SISWA SMA DI ERA NEW NORMAL - Chyntia Clarinda; Novalina; Mariana Gu; Faradiba Faradiba (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
Technological developments present many choices of learning media. The learning media that is the prima donna during the pandemic is a virtual laboratory. Virtual laboratories are used by teachers as a substitute for face-to-face practicum activities. There are many kinds of virtual laboratory applications that have been spread, one of which is the "PhET" simulation application. The purpose of this study was to determine the impact of using the PhET simulation application on improving student learning outcomes. This research was conducted at SMAN 54 Jakarta. The method used in this research is descriptive quantitative with the type of pre-experimental research. Data collection techniques used in this study were questionnaires and tests. Questionnaires and tests were used to obtain data on student learning outcomes. Data analysis used t test and N-gain test. The t-test was used to see if there was an effect of using a virtual laboratory on student learning outcomes. While the N-Gain test is to see how effective the use of virtual laboratories is to improve learning outcomes. The results of this study indicate an increase in student learning outcomes after using a virtual laboratory application.